The employers' and students' perspectives toward the generic skills of graduates as an indicator of work readiness / Norazliyati Yahya - Yahya, Norazliyati (2012)
This study examines the employers’ and students’ perspectives towards university graduates’ work readiness as indicated by their generic skills. The specific objectives of the study are 1) to examine the perception of employers and students (science and social science based) towards generic skills required and displayed by fresh graduates; 2) to examine the perception of science and social science students towards generic skills being taught at the universities; 3) to identify the mismatch between employers’ and students’ perceptions (science and social science based) toward generic skills required in terms of level of priority; and 4) to determine the priority of generic skills in term of rank as perceived by employers and students (science and social science based). This study used simple random sampling and samples of this study consist of 33 employers and 107 students. The data were collected using an instrument in the form of a questionnaire and the data was analysed using descriptive statistic analysis. From the study, the findings revealed that graduates’ generic skills were lower than the requirements of the employers and there were mismatches between the required generic skills as perceived by employers and students as found in Communication Skills, Critical Thinking and Problem Solving Skills, Leadership Skills and Lifelong Learning and Information Management. There were also mismatches between the generic skills being emphasised in the universities and generic skills displayed by graduates as perceived by employers and students as found in Teamwork Skills, Critical Thinking and Problem Solving Skills and Communication Skills. Further analysis revealed that there were also mismatches between employers’ and students’ perceptions toward generic skills required in terms of level of priority as found in Integrity and Professional Ethics, Critical Thinking and Problem Solving Skills, Teamwork Skills and Lifelong Learning and Information Management. The study suggested the rank of generic skills as perceived by employers in the final part of the analysis as an effort to improve the acquisition of generic skills amongst the students of higher education institutions. It is hoped that this study could provide significant insights and contribute to the improvement in the development and implementation of generic skills through the curriculum of the university in order to foster a better acquisition of generic skills among the university students.